2008
DOI: 10.1007/s10350-007-9137-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Risk Factors for Colonic Diverticular Hemorrhage

Abstract: Hypertension, nonsteroidal anti-inflammatory drugs, and anticoagulants, including aspirin, are independent risk factors for colonic diverticular hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 19 publications
7
117
2
3
Order By: Relevance
“…Although diverticular hemorrhage ceases spontaneously in many cases, delayed recurrent bleeding may occur in 16-38% of patients. As shown in a previous report (21), patients with diverticular bleeding often exhibit various comorbidities and have a history of antithrombotic drug use; thus, surgical intervention sometimes carries a very high risk. Therefore, identifying the source of bleeding prior to surgery using CE-CT may result in a less invasive urgent colonoscopy procedure and more effective hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although diverticular hemorrhage ceases spontaneously in many cases, delayed recurrent bleeding may occur in 16-38% of patients. As shown in a previous report (21), patients with diverticular bleeding often exhibit various comorbidities and have a history of antithrombotic drug use; thus, surgical intervention sometimes carries a very high risk. Therefore, identifying the source of bleeding prior to surgery using CE-CT may result in a less invasive urgent colonoscopy procedure and more effective hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In LG, colonic DH was the most common disorder causing LGIB. Moreover, colonic DH has also recently been reported as the most common cause of LGIB in Japan [2,12] . Compared to a few decades ago, changes in the agingassociated diseases that cause LGIB have been occurring.…”
Section: Comparison Of Specific Diseases In Eg and Lgmentioning
confidence: 96%
“…Yamada et al (11), whilst studying risk factors for CDB, also reported that the proportion of bilateral diverticulosis was larger among patients with hemorrhage, and Faucheron et al (9) and Suzuki et al (8) stated that right-sided diverticula location was associated with a significant risk of bleeding, which was independent of age. Even though right-sided diverticula are less prevalent in the western population than left-sided ones (9), these results highlight the need to monitor patients with known right-sided diverticulosis closely and to alert clinicians to the greater risk of severe bleeding in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors for CDB were identified in previous studies, namely previous episodes of CDB (7), right-sided diverticula (8,9), obesity (10), hypertension (11), diabetes mellitus, cardiovascular or cerebrovascular diseases (12). It has also been demonstrated that several medicaments are associated with an increased risk of CDB, including steroidal (13) and non-steroidal anti-inflammatory drugs (11,14,15) and antihypertensive medication (calcium-channel blockers) (13).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation